Associations between maternal adiposity and appetite-regulating hormones in human milk are mediated through maternal circulating concentrations and might affect infant outcomes - Christensen, Sophie Hilario; Lewis, Jack Ivor; Larnkjær, Anni; Frøkiær, Hanne; Allen, Lindsay H.; Mølgaard, Christian; Michaelsen, Kim F. (Frontiers in Nutrition, 2022)
Appetite-regulating hormones (ARH) in human milk (HM) are suggested to affect infants’ milk intake and possibly infant growth. Maternal adiposity might contribute to higher levels of ARH in HM, either from the mammary gland or from raised circulating levels due to higher adiposity. Counterfactual-based mediation analysis can define indirect and direct effects between HM ARH and maternal and infant factors, and might be an important tool when investigating the mother-milk-infant triad. We aim to investigate whether potential associations between 1) maternal adiposity and HM ARH and 2) HM ARH and infant milk intake and growth are mediated through maternal and infant plasma ARH, respectively. Maternal and infant anthropometry and body composition, HM and blood samples were collected from 223 mother-infant dyads participating in the Mother, Infant and Lactation Quality study at three postpartum visits from 1-8.49 months. Leptin, insulin and adiponectin were analyzed using immunoassays. Mediation analyses using linear mixed-effect models were applied to investigate the direct and indirect effects through maternal and infant plasma hormone concentrations. A positive association between maternal body-mass-index (BMI) and HM leptin was mediated by maternal plasma leptin by 29% when fixing BMI to <25kg/m2, and by 51% when fixing BMI to ≥25kg/m2 (pinteraction<0.01). There was no mediated effect through plasma insulin in the association between BMI and HM insulin (p=0.068). We found negative and positive associations between HM insulin and total milk intake and infant weight, respectively, however these diminished in mediation analyses with reduced sample sizes. Our main results suggest that the association between maternal adiposity and HM leptin was mediated through circulating leptin to a stronger degree for mothers with overweight compared to mothers with normal-weight. This indicates that excess maternal adiposity, and the resulting rise of circulating leptin and possible concomitant low-grade inflammation, may be reflected in HM composition.